2008
DOI: 10.1063/1.2832506
|View full text |Cite
|
Sign up to set email alerts
|

High thermal stability of carbon-coated L10-FePt nanoparticles prepared by salt-matrix annealing

Abstract: Monodisperse L1 0 -FePt nanoparticles with size ranging from 3 to 8 nm were prepared by the salt-matrix annealing method. It was observed that the annealed particles have high thermal stability-no sintering occurred even when the particles were heated at 1100°C for an hour. This high thermal stability resulted from carbon coating of the particles during salt-matrix annealing as consequence of decomposition of surfactants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…In this work, we focus on a different approach in the same vein, which consists of annealing of the FePt NPs in a matrix of NaCl powder. This method has been reported to efficiently prevent particles from sintering 15–17. As compared to the oxide shell growth, salt matrix annealing exhibits a higher potential to be scaled up to larger quantities due to its simplicity of realization.…”
Section: Methodsmentioning
confidence: 99%
“…In this work, we focus on a different approach in the same vein, which consists of annealing of the FePt NPs in a matrix of NaCl powder. This method has been reported to efficiently prevent particles from sintering 15–17. As compared to the oxide shell growth, salt matrix annealing exhibits a higher potential to be scaled up to larger quantities due to its simplicity of realization.…”
Section: Methodsmentioning
confidence: 99%
“…This may be attributed to the decomposition of the surfactants, as also reported in [17] and [18]. There is also indirect evidence that the broad peak was not observed in the DSC curve of the 500…”
Section: B Phase Transformation and Magnetic Hardening In Isolated Fmentioning
confidence: 63%
“…Development of Isolated L1 0 FePt Nanoparticles Our previous study showed that carbon-coated FePt particles were formed by annealing the salt-surfactant-particle mixtures, as a consequence of decomposition of the surfactants into carbon [17]. The carbon coating makes the FePt particles highly thermally stable.…”
Section: Resultsmentioning
confidence: 99%
“…To avoid this aggregation/sintering problem, FePt nanoparticles are either coated with SiO 2 [186,187], or grinded with a large excess of NaCl [188,189] before high temperature annealing is applied. In the SiO 2 coated FePt, the conversion to the fct-FePt could be seen only above 600-700°C the uncoated nanoparticles began the structure transformation at 550°C [165].…”
Section: Synthesis Of Dispersible Fct-fept Nanoparticlesmentioning
confidence: 99%